REDESIGNING A NEGATIVE SPACE THROUGH CPTED IN SUSUKINO DISTRICT, SAPPORO, JAPAN - Sylviana Putri Sunario Soegondo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2020)
As an impact of prostitution site, criminality is basically triggered by a negative space; however, prostitution site in Japan is a part of the city. Susukino in Sapporo, for example, plays a role as a tourist attraction as well as a prostitution site. This research aims to figure out how the architectural design in Susukino influences criminality prevention as an effect of prostitution site. Survey and interview were conducted to observe zonation in Susukino and to define a negative space as a problem of the district. Later, seven aspects: 1)Defensible space, 2)Territoriality, 3)Surveillance, 4)Lighting, 5)Landscaping, and 6)Physical security; based on CPTED (Crime Prevention Through Environment Design) theory were applied as a basis to propose a safe ambiance in the negative space by increasing street connectivity.